The sense of presence through the humanization created by virtual environments - Donga, João (2021)
This work focus on the study of solutions that using video 360 and virtual reality that allow children’s and older people that are away of their family environments for various reasons to be able to feel they are participating at family or school events. The solutions proposed should deliver a strong sense of presence to the users and the interface must be friendly. The validation will be made by user observation and inquiries.